Maxillary Distomolar Associated with Dentigerous Cyst: An Unusual Entity - Edouard Di Donna; Loïc Mahé Keller; Annika Neri; Alexandre Perez; Tommaso Lombardi (MDPI AG, 2022)
Supernumerary teeth may be encountered as an incidental finding on a radiograph. When impacted, they may be associated with clinical signs related to different problems such as failure of eruption, teeth displacement, root resorption or cystic lesions. They may occur in primary and permanent dentition, in both the maxilla and mandible and can be single or multiple in patients with syndromes. Mesiodens is the most commonly impacted tooth and appears between the central maxillary incisors in pediatric ages. Supernumerary teeth distal to the third molar are rare, usually impacted and referred to as a distomolar. A 46-year-old male consulted with the main complaint of pain on the left side of the maxilla. A panoramic radiograph revealed a right impacted maxillary fourth molar located posterior to the third molar associated with a pericoronal radiolucency. The supernumerary tooth was removed surgically under local anesthesia and the pericoronal lesion enucleated. Histopathological examination was consistent with the diagnosis of a dentigerous cyst associated with an impacted distomolar. Healing was uneventful, and the patients remained asymptomatic. The occurrence of an impacted maxillary distomolar is rare and even rarer the association with a dentigerous cyst.